2015
DOI: 10.1302/0301-620x.97b2.34144
|View full text |Cite
|
Sign up to set email alerts
|

Zonal fixation in revision total knee arthroplasty

Abstract: Revision knee arthroplasty presents a number of challenges, not least of which is obtaining solid primary fixation of implants into host bone. Three anatomical zones exist within both femur and tibia which can be used to support revision implants. These consist of the joint surface or epiphysis, the metaphysis and the diaphysis. The methods by which fixation in each zone can be obtained are discussed. The authors suggest that solid fixation should be obtained in at least two of the three zones and emphasise th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
103
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(115 citation statements)
references
References 28 publications
0
103
0
12
Order By: Relevance
“…При данном варианте реконструкции сложности в корректном пространственном позиционировании втулки и, соответственно, эндопротеза возникают, если диафизы бедренной или большеберцовой костей деформированы [10]. Поэтому у ряда пациентов установить удлиняющую ножку становится невозможным, и если это сочетается с дефицитом костной массы эпифиза, то компрометируется принцип достижения фиксации ревизионного имплантата как минимум в двух зонах [11]. Вместе с тем результаты использования металлических втулок с напылением (средний срок наблюдения 3,6±1,4 лет) и конусов (средний срок наблюдения 4,5±1,6 лет) показывают хорошую выживаемость имплантатов в раннем и среднесрочном периодах (97,3 и 97,8% соответственно) [12].…”
Section: Discussionunclassified
“…При данном варианте реконструкции сложности в корректном пространственном позиционировании втулки и, соответственно, эндопротеза возникают, если диафизы бедренной или большеберцовой костей деформированы [10]. Поэтому у ряда пациентов установить удлиняющую ножку становится невозможным, и если это сочетается с дефицитом костной массы эпифиза, то компрометируется принцип достижения фиксации ревизионного имплантата как минимум в двух зонах [11]. Вместе с тем результаты использования металлических втулок с напылением (средний срок наблюдения 3,6±1,4 лет) и конусов (средний срок наблюдения 4,5±1,6 лет) показывают хорошую выживаемость имплантатов в раннем и среднесрочном периодах (97,3 и 97,8% соответственно) [12].…”
Section: Discussionunclassified
“…In this scenario, obtaining a stable fixation of the revision implant is mandatory. Morgan-Jones et al [52] recently defined the "zonal fixation" concept. The femur and tibia can be divided into three zones: the joint surface or epiphysis, the metaphysis, and the diaphysis.…”
Section: Treatment Of Bone Deficiency In Revision Total Knee Arthroplmentioning
confidence: 99%
“…Traditionally such defects are managed with stemmed implants that are either fully cemented or cemented in the epiphyseal/metaphyseal area. It was suggested that appropriate implant stability can be achieved if solid fixation is attained using at least two of three defined anatomical zones of fixation (epiphysis or joint surface, metaphysis, and diaphysis) . This suggests that if adequate epiphyseal and metaphyseal implant fixation can be achieved, revision of AORI IIB defects could be done appropriately with stemless implants.…”
mentioning
confidence: 99%
“…Metaphyseal sleeves, have been introduced to compensate for severe osseous defects and provide better zonal fixation in the metaphysis . Several clinical studies with short term follow up have suggested that using the metaphyseal sleeves without stems, can provide adequate initial implant stability when reconstructing tibiae with AORI type II and III defects .…”
mentioning
confidence: 99%